Leaf Stripping to Maximize Food and Feed Yields from Maize-Based Cropping Systems, Ghana - International Institute of Tropical Agriculture (International Food Policy Research Institute, 2019)
Feed shortages during the cropping season constrain to livestock production in small-scale crop-livestock systems in northern Ghana. The effect of stripping the lower leaves of maize at tasseling and silking to feed livestock on grain and stover yields of maize was tested over two years in northern Ghana.